Synthesis and Characterization of Cobalt Oxide Nanoparticles and Cobalt Oxide/MWCNTs as a Binary Nanocomposite - Safa Yassin; Haider Ghrabee; Donia Abdulateef (College of Education for Pure Sciences, 2024)
There is a rising interest in nanocomposites with unanticipated features that are different from traditional materials to fulfill the demands of these applications. Cobalt oxide (Co3O4) nanoparticles, and cobalt oxide with multi-walled carbon nanotubes (Co3O4/ MWCNTs) as nanocomposites were created. In this study, cobalt oxide nanoparticles (Co3O4 NPs) were synthesized via co-precipitation method chemical using CoCl2 salt as a source of cobalt nanoparticles and sodium hydroxide solution as a factor agent at room temperature. The cobalt hydroxide (Co(OH)2) precipitate was obtained, then it calcinated the cobalt hydroxide precipitate at 600°C to obtain the cobalt oxides nanoparticles (Co3O4 NPs). Also, MWCNTs were prepared by a locally manufactured reactor at 423 k. Binary composites were prepared by solution method using cobalt oxide nanoparticles dispersion over MWCNTs surfaces. The structural, morphological, and spectral properties were confirmed and investigated by using FE-SEM, Raman spectroscopy, and (XRD), respectively. The surface area and pore size obtained by BET and BJH showed that the binary nanocomposites (Co3O4/MWCNTs) have a higher surface area than their pristine cobalt oxide and multi-walled carbon nanotubes nanoparticles. The adsorption processes of nanocomposites have attracted significant care from the scientific public because of their distinctive possessions and aptitude to reduce and adsorb Cu+2 and Ni+2 as heavy metals from water pollution. As a result, Co3O4 and its nanocomposite with MWCNTs were used to remove copper and nickel ions from the dilute aqueous solution.